A comparative study using polymerase chain reaction, cultivation and immuno-magnetic separation for detection, isolation, and identification of Legionella spp. in water and biofilm samples from groundwaters. - Brooks, Teresa Jane. (University of Ottawa (Canada), 2001)
This study was carried out to determine the frequency and levels of occurrence of legionellae in groundwaters from a variety of sources in U.S. and Canada. A limited number of water samples from cooling towers were also tested because municipally treated waters are considered to be the main sources of Legionella in artificial habitats such as cooling towers, air conditioners, whirlpools, hot tubs and plumbing systems (Krammer and Ford, 1994). Conventional procedures, including cultivation and polymerase chain reaction (PCR), were used to determine the presence of Legionella spp. in the water and biofilm samples during this study. A novel approach, using immuno-magnetic separation (IMS) in combination with cultivation or PCR, was also explored as an improved and rapid detection method for Legionella over conventional procedures. Because the IMS technique was continually being improved over the course of this study, all the samples received did not undergo the same procedure. (Abstract shortened by UMI.)
Keywords: Biology, Microbiology.